Pengaruh PDB, Inflasi, Tingkat Suku Bunga dan Nilai Tukar Rupiah terhadap Indeks Harga Saham JAKPROP yang Terdaftar di Bursa Efek Indonesia - Chendra Gunawan; Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
This research aims to find out and analyze the effects of variable GDP, Inflation, Interest rates, Exchange rate on share prices of listed property sector in Indonesia Stock Exchange. The object population in this study is a company incorporated in the listed Property & Real Estate Index sector (JAKPROP) in Indonesia Stock Exchange (BEI) from 2008 to 2017. This study uses Ordinary Least Square analysis to determine the effect of independent variables on the Property & Real Estate Index sector JAKPROP. Based on t test, GDP is significant, Inflation is not significant and BI Interest rate is significant effect, while the variable Exchange rate have a significant effect on property and Real Estate sector stock price index. Results simultaneously with the F test showed that all the independent variable significantly influenced on the stock price index Property & Real Estate sector. So, the result is the independen variable GDP, Bi-rate & Exchange-rate has an influence effect on the stock price index of listed Property & Real Estate sector JAKPROP in Indonesia Stock Exchange.